In Vitro Echinocandin Susceptibility of Aspergillus Isolates from Patients Enrolled in the Transplant-Associated Infection Surveillance Network - Lockhart, Shawn R. (American Society for Microbiology, 2011)
We determined the echinocandin minimum effective concentration (MEC) values for caspofungin, micafungin, and anidulafungin against 288 Aspergillus isolates prospectively collected from transplant patients with proven or probable invasive aspergillosis between 2001 and 2006 as part of the Transplant-Associated Infection Surveillance Network (TRANSNET). We demonstrated that the vast majority of Aspergillus isolates had MEC values at or below the epidemiological cutoff values for caspofungin, micafungin, and anidulafungin, including those from patients who had received caspofungin.